(5/6c)-(3/4)=(11/12)

Simple and best practice solution for (5/6c)-(3/4)=(11/12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5/6c)-(3/4)=(11/12) equation:


c in (-oo:+oo)

(5/6)*c-(3/4) = 11/12 // - 11/12

(5/6)*c-(3/4)-(11/12) = 0

(5/6)*c-3/4-11/12 = 0

5/6*c-5/3 = 0 // + 5/3

5/6*c = 5/3 // : 5/6

c = 5/3/5/6

c = 2

c = 2

See similar equations:

| 2(5+2x)+4=26 | | -4x+3=x+18u | | 24b^3-18b^2=0 | | 3(x+3)+2=17 | | 15x+2=28 | | V=S*(P*0.018+0.5) | | x+0.46x= | | 5(-2x-9)+12(4+x)=18 | | (mn)-3= | | Vout=Vs*(P*0.018+0.5) | | 8x+27=6x+57 | | 16/3t-23/5 | | 10-(3+2)= | | y=20x+900 | | 6q=45+q | | 5x+1-7x= | | 1/6n-5 | | -3z-4+2z=5 | | 5/4n=6 | | 4/4n=6 | | 9(x-8)-13=5 | | 8x-64=8 | | 2/4n=6 | | 2(1x+4)-1=15 | | Vout=Vs(P*0.018+0.5) | | 5x=-2x+25 | | 55+(4x-5)=x | | (x-598)=0 | | 4x-18=3x+9 | | 7x+21=91 | | 116-31=x | | 5x+0.5y+1z=100 |

Equations solver categories